Feasibility of an E-Module Based on Problem-Based Learning Combined with Socratic Dialogue to Enhance Students' Critical Thinking Skills - Pitorini, Dewi Ekaputri; Suciati, Suciati; Harlita, Harlita (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2024)
Learning in the 21st century requires the use of technology. E-modules are one form of utilizing technology as a medium for teaching materials. The research aims to test the feasibility of an e-module based on problem-based learning combined with Socratic dialogue to enhance critical thinking skills. Feasibility test includes validity testing and practicality testing of e-modules. The e-module validity test was carried out by three expert validators, namely material expert validators, learning media experts, and learning instrument experts. The practicality test aims to determine the responses from educational practitioners and e-module users. The instrument used to assess the feasibility of e-modules was a questionnaire. The feasibility test results in the form of assessment scores were analyzed quantitatively. The results of the e-module validity test obtained a total average score of 92.67 (very good). The results of the e-module practicality test obtained a total average score of 92.66 (very good). The e-module based on PBL combined with Socratic dialogue has a very good level of feasibility and is suitable for application in the classroom.ABSTRAK: Pembelajaran di abad 21 menuntut adanya pemanfaatn teknologi. E-modul adalah salah satu bentuk pemanfaatan teknologi sebagai media bahan ajar. Penelitian bertujuan untuk menguji kelayakan e-modul berbasis Problem-Based Learning dipadu Dialog Socrates untuk memberdayakan kemampuan berpikir kritis. Uji kelayakan meliputi uji validitas dan uji kepraktisan e-modul. Uji validitas e-modul dilakukan oleh tiga validator ahli, yaitu validator ahli materi, ahli media pembelajaran, dan ahli instrumen pembelajaran. Uji kepraktisan bertujuan untuk mengetahui respon dari praktisi pendidikan dan pengguna e-modul. Instrumen yang digunakan untuk menilai kelayakan e-modul adalah angket. Hasil uji kelayakan berupa skor penilaian dianalisis secara kuantitatif. Hasil uji validitas e-modul memperoleh nilai rata-rata total sebesar 92,67 (sangat baik). Hasil uji kepraktisan e-modul memperoleh nilai rata-rata total sebesar 92,66 (sangat baik). E-modul berbasis Problem-Based Learning dipadu Dialog Socrates memiliki tingkat kelayakan yang sangat baik dan layak untuk diterapkan di kelas.